The need for planning career civil servants in Kazakhstan (Journal of Economic Research & Business Administration, 2016)
In this article the authors consider a system of planning career civil ser- vants. The article reveals the need for the formation of a professional state apparatus based on the use of modern technology staff to ensure effective and transparent procedures for admission to the civil service, consistent and fair promotion of the career ladder. The main problem is the lack of qualified specialists in the field of public service, formation of personnel reserve managers and personnel reserve system work ended. In this re- gard, the conclusion the authors propose a range of measures to address the problems identified. It should be noted that the introduction of a new mechanism of career civil servants should be aimed at the development of personnel management system.. The main component of personnel policy should be the daily work of every civil servant at all stages of his career with the progressive advancement of human technology.
Keywords: civil servants; personnel policies; career planning; public administration; career growth; human resource management